2001
DOI: 10.1017/s0022112001005109
|View full text |Cite
|
Sign up to set email alerts
|

Non-axisymmetric instability of centrifugally stable stratified Taylor–Couette flow

Abstract: The stability is investigated of the swirling flow between two concentric cylinders in the presence of stable axial linear density stratification, for flows not satisfying the well-known Rayleigh criterion for inviscid centrifugal instability, d(Vr)2/dr < 0. We show by a linear stability analysis that a sufficient condition for non-axisymmetric instability is, in fact, d(V/r)2/dr < 0, which implies a far wider range of instability than previously identified. The most unstable modes are radially smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 22 publications
10
91
1
Order By: Relevance
“…Further away from the threshold, the 2D-Fourier transforms are more complex and indicate other peaks, but in the following we only focus on the most energetic of them. As suggested by the analytical study of Shalybkov and Rüdiger [13], we did not observe any systematic variation of the wavenumber k = 2π q (R i (R o − R i )) 1/2 : over all our experiments, we measure a mean value of 10.6 with a standard variation of 1.5 in close agreement with analytical and numerical results [12,13]. This value corresponds to a wavelength equal to 1.17 time the gap, smaller than the standard value in the absence of stratification (i.e.…”
supporting
confidence: 90%
“…Further away from the threshold, the 2D-Fourier transforms are more complex and indicate other peaks, but in the following we only focus on the most energetic of them. As suggested by the analytical study of Shalybkov and Rüdiger [13], we did not observe any systematic variation of the wavenumber k = 2π q (R i (R o − R i )) 1/2 : over all our experiments, we measure a mean value of 10.6 with a standard variation of 1.5 in close agreement with analytical and numerical results [12,13]. This value corresponds to a wavelength equal to 1.17 time the gap, smaller than the standard value in the absence of stratification (i.e.…”
supporting
confidence: 90%
“…This corresponds to the local approximation of the Keplerian flow for which both flows possess the same shearto-rotation ratio Ω /Om (Ω being the angular velocity) equal to −3/2. The stability properties of the flow in this small-gap limit have been obtained in Yavneh et al (2001) and Dubrulle et al (2005b). We shall see that they sensibly differ from those obtained for an unbounded Keplerian flow.…”
Section: Base Flow and Perturbation Equationsmentioning
confidence: 76%
“…Small-gap configurations have been considered by Yavneh et al (2001) who have shown that the flow is unstable when the fluid is sufficiently stratified. In figure 1, results for a large-gap configuration (d = 5) are plotted.…”
Section: Effect Of the Finite Gap Sizementioning
confidence: 99%
“…This means that all anti-cyclonic flows are potentially linearly unstable. The role of dissipation on the instability has been studied numerically [41,42]) and experimentally [43,44]. It was found that stratification stabilizes the flow in the GSPC regime, while it destabilizes it in the GSBC anti-cyclonic regime.…”
Section: Vertical Stratificationmentioning
confidence: 99%